VISLIX: An XAI Framework for Validating Vision Models with Slice Discovery and Analysis - Yan, Xinyuan; Xuan, Xiwei; Ono, Jorge Piazentin; Guo, Jiajing; Mohanty, Vikram; Kumar, Shekar Arvind; Gou, Liang; Wang, Bei; Ren, Liu (Computer graphics forum, 2025)
Real‐world machine learning models require rigorous evaluation before deployment, especially in safety‐critical domains like autonomous driving and surveillance. The evaluation of machine learning models often focuses on data slices, which are subsets of the data that share a set of characteristics. Data slice finding automatically identifies conditions or data subgroups where models underperform, aiding developers in mitigating performance issues. Despite its popularity and effectiveness, data slicing for vision model validation faces several challenges. First, data slicing often needs additional image metadata or visual concepts, and falls short in certain computer vision tasks, such as object detection. Second, understanding data slices is a labor‐intensive and mentally demanding process that heavily relies on the expert's domain knowledge. Third, data slicing lacks a human‐in‐the‐loop solution that allows experts to form hypothesis and test them interactively. To overcome these limitations and better support the machine learning operations lifecycle, we introduce VISLIX, a novel visual analytics framework that employs state‐of‐the‐art foundation models to help domain experts analyze slices in computer vision models. Our approach does not require image metadata or visual concepts, automatically generates natural language insights, and allows users to test data slice hypothesis interactively. We evaluate VISLIX with an expert study and three use cases, that demonstrate the effectiveness of our tool in providing comprehensive insights for validating object detection models.